1993
DOI: 10.1111/j.1471-4159.1993.tb03575.x
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Development and Postnatal Changes in Free d‐Aspartate and d‐Serine in the Human Prefrontal Cortex

Abstract: We have analyzed free chiral amino acids (aspartate and serine) in the human frontal cortex at different ontogenic stages (from 14 weeks of gestation to 101 years of age) by HPLC with fluorometric detection after derivatization with N-tert-butyl-oxycarbonyl-L-cysteine and o-phthaldialdehyde. Exceptionally high levels of free D-aspartate and D-serine were demonstrated in the fetal cortex at gestational week 14. The ratios of D-aspartate and of D-serine to the total corresponding amino acids were also high, at 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
174
0
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(178 citation statements)
references
References 28 publications
1
174
0
2
Order By: Relevance
“…It occurs in selected neuronal populations in the brain. Although the levels of D-aspartate are highest in early life, adult brain levels of D-aspartate are greater than those of acetylcholine, norepinephrine, dopamine and serotonin (Schell et al, 1997a;Hashimoto et al, 1993c). D-aspartate is concentrated particularly in the supraoptic and paraventricular neurons of the hypothalamus and is contained in the fibers from these cells that innervate the posterior pituitary (Schell et al, 1997a).…”
Section: Discussionmentioning
confidence: 99%
“…It occurs in selected neuronal populations in the brain. Although the levels of D-aspartate are highest in early life, adult brain levels of D-aspartate are greater than those of acetylcholine, norepinephrine, dopamine and serotonin (Schell et al, 1997a;Hashimoto et al, 1993c). D-aspartate is concentrated particularly in the supraoptic and paraventricular neurons of the hypothalamus and is contained in the fibers from these cells that innervate the posterior pituitary (Schell et al, 1997a).…”
Section: Discussionmentioning
confidence: 99%
“…Neurophysiological studies of expressed NMDA receptors indicate that with certain combinations of NR1 and NR2 subunits, D-serine is up to three times more potent than glycine at the glycine site (Matsui et al, 1995;Priestley et al, 1995). Although D-amino acids have long been known to exist in bacteria, worms, and insects (Corrigan, 1969), only very recently have high levels of D-serine been demonstrated in mammalian tissues, especially in the brain (Hashimoto et al, 1992a(Hashimoto et al, , 1993aNagata, 1992;Chouinard et al, 1993;Nagata et al, 1994).We have mapped D-serine immunohistochemically in rat brain and observed a pattern that parallels the localization of D-serine binding sites associated with NMDA receptors in the forebrain (Schell et al, 1995). D-Serine is concentrated in gray matter regions enriched in NMDA receptors and is selectively localized to protoplasmic astrocytes.…”
mentioning
confidence: 99%
“…Consistent with a neurodevelopmental hypothesis of SCZ, 12,61 a putative precocious downregulation of D-Asp levels, associated to abnormal metabolism of this molecule, may have a much greater impact during critical phases of brain development, when D-Asp levels are physiologically high. 13,14,16 Future studies in mouse models permitting controlled exposure of D-Asp levels during neurodevelopment are warranted to investigate this basic issue.…”
Section: Discussionmentioning
confidence: 99%
“…12 Free D-aspartate (D-Asp) is present in markedly high amounts in the embryonic brain of mammals. After birth, the endogenous levels of this atypical amino acid rapidly decrease, [13][14][15][16] due to the onset of the D-aspartate oxidase (DDO) activity. 17 Recent evidence has shown that D-Asp activates NMDARs through the binding to the glutamate site of GluN2 subunits.…”
Section: Introductionmentioning
confidence: 99%